MOTIVASI BELAJAR: OPTIMALISASI DARI MODEL PEMBELAJARAN CORE - Nanda Ramadhani; Heru Juabdin Sada; Erni Yusnita (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to examine the effectiveness of the CORE (Connecting, Organizing, Reflecting, Extending) learning model in enhancing students’ motivation to learn Akidah Akhlak at MAN 2 Bandar Lampung, particularly regarding hope and future aspirations. The study employed a quasi-experimental design using a Posttest-Only Control Group Design. The sample was selected through simple random sampling, consisting of an experimental class applying the CORE model and a control class receiving conventional instruction. Data were collected using a validated and reliable 15-item learning motivation questionnaire. The results indicate a statistically significant difference between the two groups, with higher motivation scores in the experimental class. The key finding reveals that integrating CORE stages systematically strengthens students’ future-oriented motivation. It is concluded that the CORE model is effective in fostering intrinsic motivation beyond cognitive outcomes. Study implies that teachers should design reflective and meaningful learning experiences that connect instructional content with students’ personal aspirations.